Peran Kepala Sekolah Sebagai Manajer dalam Meningkatkan Kinerja Guru Di SD negeri Tanjungsari 01 Kecamatan Wanasari Kabupaten Brebes - Negara, Wiwik Sundari Cinta; Wuryandini, Endang; Rasiman, Rasiman (PGRI Kota Semarang, 2024)
This research was motivated by the success of the principal of SD Negeri Tanjungsari 01, Wanasari District, Brebes Regency in carrying out his role as a manager, so that the school became a pilot school for P5 activities at the district level. The focus of this research is the role of the principal as a manager in improving teacher performance at SD Negeri Tanjungsari 01, Wanasari District, Brebes Regency. The sub-focus includes 1) The principal's planning in improving teacher performance at Tanjungsari State Elementary School 01. 2) The principal's organization in improving teacher performance at Tanjungsari State Elementary School 01. 3) The principal's implementation in improving teacher performance at Tanjungsari State Elementary School 01. 4) Supervision of the principal in improving teacher performance at SD Negeri Tanjungsari 01. The aim of this research is to describe and analyze the planning, organization, implementation and supervision of school principals in improving teacher performance. The utility of this research were theoretical and practical benefits. The theoretical benefits are expected to be useful for the development of educational management science, namely increasing knowledge, experience and insight as well as as study and supporting material. Practical benefits are for teachers, schools and education services . The research method is a qualitative approach and a case study type of research using data collection instruments in the form of observation, interviews and documentation methods. Data analysis is carried out through the process of data collection, data reduction, data presentation and drawing conclusions. Meanwhile, data validation uses triangulation techniques The results of the research show that the role of the principal as a manager in improving teacher performance at SDN Tanjungsari 01, Wanasari District, Brebes Regency is carried out with structured management from planning, organizing, implementing and monitoring, although there are still obstacles but they can be resolved well. The principal in carrying out the manager's function is carried out well by involving all stakeholders in every activity; coaching for teachers; implementation of good cooperation and collaboration; Performance improvement through scientific forums. From the research results, it is recommended that efforts be made to provide enthusiasm and motivation to teachers in increasing teacher professionalism as well as; curriculum development; provide encouragement to continue studies; providing facilities; setting a good working climate. Keywords: Role of the Principal, Manager Function, Teacher Performance